Membangun Kepuasan Konsumen melalui Kepercayaan Merek, Fasilitas, dan Kualitas Pelayanan: Studi pada Susu Moeria Cafe Kudus - Septia Nurul Uyun; Kusumantoro Kusumantoro (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of brand trust, facilities, and service quality on consumer satisfaction. The object of this study is Moeria Cafe Kudus, located at Jl. Pemuda No.64, Magersari, Panjunan, Kec. Kota Kudus, Kabupaten Kudus, Jawa Tengah 59312. This study adopts a quantitative approach with a causal design aimed at identifying the cause-and-effect relationship between variables. The population in this study is Moeria Cafe Milk consumers. The sampling technique used is purposive sampling using the Lemeshow formula to determine the number of research samples. This study has 100 samples or respondents. This study used validity and reliability tests to ensure the validity of the data. This study used statistical analysis and multiple linear regression techniques using IBM SPSS Statistics 25.0. The results of this study indicate that there is a positive and significant influence, both partial and simultaneous, between brand trust, facilities, and service quality on the satisfaction of Moeria Cafe Milk consumers in Kudus.